Phonological theory : the essential readings - Goldsmith, John A. (Malden, Massachusetts : Blackwell Publishers, 1999)
This volume provides a comprehensive collection of the key readings in phonological theory. It covers the main areas of phonological research, including autosegmental phonology, syllable structure, lexical phonology and metrical phonology.
Includes bibliographical references and index.
Keywords: Grammar, Comparative and general -- Phonology; Phonologie; 17.54 phonology